Clinical utility of inflammatory biomarkers in COVID-19 in direct comparison to other respiratory infections-A prospective cohort study. - Maurin Lampart; Núria Zellweger; Stefano Bassetti; Sarah Tschudin-Sutter; Katharina M Rentsch; Martin Siegemund; Roland Bingisser; Stefan Osswald; Gabriela M Kuster; Raphael Twerenbold (PLoS ONE, 2022)
Background Inflammatory biomarkers are associated with severity of coronavirus disease 2019 (COVID-19). However, direct comparisons of their utility in COVID-19 versus other respiratory infections are largely missing. Objective We aimed to investigate the prognostic utility of various inflammatory biomarkers in COVID-19 compared to patients with other respiratory infections. Materials and methods Patients presenting to the emergency department with symptoms suggestive of COVID-19 were prospectively enrolled. Levels of Interleukin-6 (IL-6), c-reactive protein (CRP), procalcitonin, ferritin, and leukocytes were compared between COVID-19, other viral respiratory infections, and bacterial pneumonia. Primary outcome was the need for hospitalisation, secondary outcome was the composite of intensive care unit (ICU) admission or death at 30 days. Results Among 514 patients with confirmed respiratory infections, 191 (37%) were diagnosed with COVID-19, 227 (44%) with another viral respiratory infection (viral controls), and 96 (19%) with bacterial pneumonia (bacterial controls). All inflammatory biomarkers differed significantly between diagnoses and were numerically higher in hospitalized patients, regardless of diagnoses. Discriminative accuracy for hospitalisation was highest for IL-6 and CRP in all three diagnoses (in COVID-19, area under the curve (AUC) for IL-6 0.899 [95%CI 0.850-0.948]; AUC for CRP 0.922 [95%CI 0.879-0.964]). Similarly, IL-6 and CRP ranged among the strongest predictors for ICU admission or death at 30 days in COVID-19 (AUC for IL-6 0.794 [95%CI 0.694-0.894]; AUC for CRP 0.807 [95%CI 0.721-0.893]) and both controls. Predictive values of inflammatory biomarkers were generally higher in COVID-19 than in controls. Conclusion In patients with COVID-19 and other respiratory infections, inflammatory biomarkers harbour strong prognostic information, particularly IL-6 and CRP. Their routine use may support early management decisions.